2021
DOI: 10.7759/cureus.14036
|View full text |Cite
|
Sign up to set email alerts
|

Patients’ Attitudes and Sources of Information on Coronavirus Disease 2019 in Rural Michigan

Abstract: Background This study investigated patients’ attitudes about severe acute respiratory syndrome coronavirus 2 in rural Michigan. Despite increasing cases in rural communities across America, surveys have revealed that residents may feel less threatened by the virus compared to their urban counterparts. This difference in attitude and information appraisal can negatively affect rural health by discouraging coronavirus disease (COVID-19) preventative behaviors. Understanding social influences that cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 11 publications
1
0
0
Order By: Relevance
“…Participants across our samples listed local sources such as friends, family members, local news, physicians, or other health care professionals as their most used sources of information on COVID-19. This finding is consistent with studies that found that facilitating relationships with local stakeholders and health care providers is essential for building trust in COVID-19, especially in rural communities [42,43]. To increase people's trust in message sources, we recommend including contact information and a specific link to learn more about the health issue as well as using a knowledgeable spokesperson such as a community physician to disseminate new health messages [44].…”
Section: Principal Findingssupporting
confidence: 82%
“…Participants across our samples listed local sources such as friends, family members, local news, physicians, or other health care professionals as their most used sources of information on COVID-19. This finding is consistent with studies that found that facilitating relationships with local stakeholders and health care providers is essential for building trust in COVID-19, especially in rural communities [42,43]. To increase people's trust in message sources, we recommend including contact information and a specific link to learn more about the health issue as well as using a knowledgeable spokesperson such as a community physician to disseminate new health messages [44].…”
Section: Principal Findingssupporting
confidence: 82%